"We regret to inform you that you did not match": Reflections on how to improve the match experience (Canadian Medical Education Journal, 2020)
Background: With the increasing awareness and action amongst stakeholders in addressing the concerning rise of unmatched Canadian Medical Graduates (CMGs), little is known from those who go unmatched. We use our unmatched experience to contribute to this dialogue.Methods: We present an issues-based examination of the matching process by reflecting on the pre- and post-match period, providing suggestions related to the Canadian context from the unmatched perspective. Results: The challenge in the pre-match period was handling uncertainty in elective scheduling. This uncertainty was largely manifested from not knowing elective availability at the time of elective application submission, as well as not knowing what “strategy” we should follow in how to structure our elective schedule. For the post-matched period, we were challenged by making decisions during a time-sensitive period, deciding on career issues like scheduling post-match electives, handling our finances, and trying to improve our future residency applications without feedback.Conclusion: Providing a real-time document of elective availability, providing focused feedback from our residency applications, and implementing and expanding upon extended curriculums for all medical schools to continue CMG training for their unmatched students for upcoming match cycles would greatly improve the unmatched experience.